Finite element analysis of concrete slab exposed to high velocity pressure wave – simplified vs. smoothed-particle hydrodynamics (SPH) method - Jindra, Daniel; Hradil, Petr; Kala, Jiří (EDP Sciences, 2024)
Many structures are required to sustain the structural resistance also under extreme loading conditions, for example impacts of high-velocity objects (airplane crash into nuclear power plant), impacts of projectiles (defence structures), or while exposed to high velocity pressure wave caused e.g. by explosion of various chemicals in industry, nature gas, or also conventional weapons. Numerical analyses of these phenomena are feasible while utilizing explicit approach of the finite element method (FEM), available in commercially accessible software LS-Dyna. In order to predict the behaviour of the structure properly, advanced nonlinear material models are required to be considered, which are often mathematically described by numerous input parameters. Several approaches to model the exposure to blast load exist, from simplified, where the blast wave is considered as timedependent pressure based on empirical equations, to more advanced ones, where the propagation of the pressure wave itself through the surrounding environment is being modelled Arbitrary Lagrangian Eulerian, (ALE method), or so called smoothed-particle hydrodynamics (SPH) method, which might be used to model the blast itself. In this paper, FEM analyses of a simply supported concrete slab with basalt fibre reinforced polymer (BFRP) bars exposed to close range explosion of TNT charge are presented. 3D numerical models are analysed utilizing explicit solver of LS-Dyna. Karagozian and Case (K&C) nonlinear material model for concrete is used, which is suitable when high strain rates are present in the quasi brittle materials. Two variants of the blast loads modelling are compared. The simplified empirical approach, which is less demanding on computational power, and feasible for utilization in case of simple structure geometry, and more demanding method using SPH method to model the TNT detonation and interaction with the exposed concrete slab. The results of these numerical analyses are compared with experimental data based on available literature, and properly discussed.

Many structures are required to sustain the structural resistance also under extreme loading conditions, for example impacts of high-velocity objects (airplane crash into nuclear power plant), impacts of projectiles (defence structures), or while exposed to high velocity pressure wave caused e.g. by explosion of various chemicals in industry, nature gas, or also conventional weapons. Numerical analyses of these phenomena are feasible while utilizing explicit approach of the finite element method (FEM), available in commercially accessible software LS-Dyna. In order to predict the behaviour of the structure properly, advanced nonlinear material models are required to be considered, which are often mathematically described by numerous input parameters. Several approaches to model the exposure to blast load exist, from simplified, where the blast wave is considered as timedependent pressure based on empirical equations, to more advanced ones, where the propagation of the pressure wave itself through the surrounding environment is being modelled Arbitrary Lagrangian Eulerian, (ALE method), or so called smoothed-particle hydrodynamics (SPH) method, which might be used to model the blast itself. In this paper, FEM analyses of a simply supported concrete slab with basalt fibre reinforced polymer (BFRP) bars exposed to close range explosion of TNT charge are presented. 3D numerical models are analysed utilizing explicit solver of LS-Dyna. Karagozian and Case (K&C) nonlinear material model for concrete is used, which is suitable when high strain rates are present in the quasi brittle materials. Two variants of the blast loads modelling are compared. The simplified empirical approach, which is less demanding on computational power, and feasible for utilization in case of simple structure geometry, and more demanding method using SPH method to model the TNT detonation and interaction with the exposed concrete slab. The results of these numerical analyses are compared with experimental data based on available literature, and properly discussed.
Finite element analysis of concrete slab exposed to high velocity pressure wave – simplified vs. smoothed-particle hydrodynamics (SPH) method
Keywords: Concrete; SPH; finite element analysis; impact loading; Concrete; SPH; finite element analysis; impact loading